Sensitive determination of bismuth by flame atomic absorption spectrometry using atom trapping in a slotted quartz tube and revolatilization with organic solvent pulse - Kilinc, Ersin; Bakirdere, Sezgin; Aydin, Firat; Ataman, O. Yavuz (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Sensitivity of flame atomic absorption spectrometry (FAAS) for Bi determination was improved by slotted quartz tube (SQT) that was used also for atom trapping (AT). The trapped analyte was released by aspirating a small volume of organic solvent after a reasonable analyte collection time. Sensitivity was improved by 2.9 times by SQT-FAAS and 256 times by SQT-AT-FAAS with respect to FAAS. Optimum trapping period was found to be 6.0 min (36.0 mL of solution). Limit of detection (LOD) for SQT-AT-FAAS was found to be 1.6 ng mL(-1). %RSD was calculated as 4.0% for five replicate measurements of 7.5 ng mL(-1) Bi by SQT-AT-FAAS. Accuracy of the method developed was checked by analyzing a standard reference material of simulated fresh water (NIST 1643e) and result found was in good agreement with the certified one. The method can be applied in any laboratory equipped with a flame AA spectrometer. The consumption of time and sample volume is fairly low and application is simple and easy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Bismuth; Slotted quartz tube; Atom trapping; Flame AAS; CLOUD POINT EXTRACTION; ENVIRONMENTAL-SAMPLES; SPECTROPHOTOMETRIC DETERMINATION; TRACE-ELEMENTS; WATER SAMPLES; GENERATION; AAS; PRECONCENTRATION; INTERFERENCE; SYSTEM; Spectroscopy